Decoding audience interpretations of awareness campaign messages. (13th June 2016) - Reid, Rayne; Van Niekerk, Johan
Abstract : Purpose: This research aims to determine whether the educational influence of the cybersecurity awareness campaign on the audience (their knowledge, behaviour and potential cybersecurity culture) matches the campaign's educational objectives. The research focuses on the knowledge component of this metric by examining the awareness campaign audience's interpretative role in processing the campaign content, through the lens of active audience theory (AAT). Design/methodology/approach: Using reflective practices, this research examines a single longitudinal case study of a cybersecurity awareness and education campaign which aims to raise awareness amongst school learners. Artefacts from a single sample are examined. Findings: Reflexive practices using theories such as active audience can assist in identifying deviations between the message a campaign intends to communicate and the message that the campaign audience receives. Research limitations/implications: Using this research approach, measurements could only be obtained for campaign messages depicted in artefacts. Future interventions should be designed to facilitate a more rigorous analysis of the audiences' interpretation of all campaign messages using ATT. Originality/value: This paper applied principles of ATT to examine the audience's interpretative role in processing an awareness campaign's content based on artifacts they created after exposure to the campaign. Conducting such analyses as part of a reflective process between cyber awareness/education campaign cycles provides a way to identify areas or topics within the campaign that require corrective action.